Pengaruh Faktor-Faktor Pemeriksaan Internal Terhadap Peningkatan Keandalan Struktur Pengendalian Internal Pada PDAM Gwar Gwamar - Ali Amin Kalau; Trisna Sary Lewaru; Stivan H Uniberua (Accounting Research Unit (ARU Journal), 2021)
The problem of the reliability of the internal control structure is thought to be one of thecauses of the not optimal performance of PDAM Gwar Gwamar in contributing to RegionalOriginal Revenue (PAD) for Aru Islands Regency. For this reason, researchers tried toexamine this problem in terms of 9 (nine) internal audit factors, including Independence,Professional Expertise, Scope of Activities, Implementation of Audit Activities, Managementof the Internal Audit Section, Work Experience, Inspection Frequency, Number of InternalAuditor Staff, and the technology used. The population in this study used the census methodwith saturated sampling technique. Data collection was carried out using survey techniquesthrough distributing questionnaires to all leaders, employees and staff of examiners/auditorsas respondents. Primary data from questionnaires were analyzed using multiple linearregression analysis. The results showed that of the overall internal control factors, only thenumber of internal auditor staff factors had no effect on the reliability of the internal controlstructure